Corporate location policy in the age of globalization - Palm, Andreas (Journal of Business Economics and Management, 2005)
In today's economy it is very important how companies select locations for headquarters, production sites and sales offices. This paper places particular emphasis on the effects on corporate location policy resulting from a constantly proceeding globalization. Therefore the term globalization is defined first. Then, using a globally present company as an example the process of deciding on locations is illustrated. Finally, there is an outlook on future demands globalization will place on corporate location policy.First published online: 14 Oct 2010